Integration of Case Study-Based Experiential Learning to Improve Communication Skills and the Depth of Thinking of Vocational Students - Rindrania, Desi; Hariyanto, Hariyanto; Priawasana, Endra (Universitas Muhammadiyah Mataram, 2026)
Despite the high demand for interpersonal excellence in the tourism industry, student engagement in Vocational High Schools remains hindered by conventional one-way instructional methods. This creates a critical gap between classroom outputs and the professional communication and analytical depth required by the sector. While Experiential Learning is a recognized pedagogical framework, its specific integration with case-study-based approaches to address the dual challenges of communication and cognitive complexity in Tourism Service programs remains under-explored. This study adopts a quasi-experimental non-equivalent control group design to evaluate the efficacy of case-study-based Experiential Learning. Involving 65 students from a Tourism Service Business Expertise Program in East Java, the research design balances rigorous statistical testing with conceptual alignment to vocational needs. Data were gathered through structured communication observations and SOLO Taxonomy-based essay tests to capture multifaceted cognitive growth. Analysis utilized Independent Samples t-test, Mann–Whitney U test, and Cohen’s d to ensure both statistical significance and practical effect size. Results indicate a significant divergence between the experimental and control groups (p < 0.001), with the experimental group demonstrating superior outcomes in both variables. The calculated effect sizes confirm a robust impact, suggesting that this integration is not merely an alternative, but a necessary instructional shift. The study's novelty lies in demonstrating how the case-study-based experiential model acts as a catalyst for transforming passive vocational learners into industry-ready communicators with higher-order thinking depth, providing a scalable strategy for modernizing vocational tourism curricula.